2004
DOI: 10.1007/s00122-004-1685-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of simple sequence repeat (SSR) markers from wheat expressed sequence tags (ESTs)

Abstract: The increasing availability of expressed sequence tags (ESTs) in wheat ( Triticum aestivum) and related cereals provides a valuable resource of non-anonymous DNA molecular markers. We examined 170,746 wheat ESTs from the public (International Triticeae EST Cooperative) and Génoplante databases, previously clustered in contigs, for the presence of di- to hexanucleotide simple sequence repeats (SSRs). Analysis of 46,510 contigs identified 3,530 SSRs, which represented 7.5% of the total number of contigs. Only 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
89
3
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 27 publications
29
89
3
4
Order By: Relevance
“…This higher polymorphism level for gSSRs was expected, because it is known that genomic DNA has higher variability than the more conserved transcribed region (Nicot et al, 2004). Another reason for lower polymorphism levels of the new SSRs is more likely to be their repeats motifs.…”
Section: Discussionmentioning
confidence: 75%
“…This higher polymorphism level for gSSRs was expected, because it is known that genomic DNA has higher variability than the more conserved transcribed region (Nicot et al, 2004). Another reason for lower polymorphism levels of the new SSRs is more likely to be their repeats motifs.…”
Section: Discussionmentioning
confidence: 75%
“…The frequency of EST-SSRs was 13.1%. Previous studies have shown that the EST-SSR frequencies of ginkgo, jatropha, poplar, and eucalyptus are 5.97, 6.51, 17.73, and 17.73%, respectively (Nicot et al, 2004;Yadav et al, 2011). The results of our present study differ markedly from these previous findings, possibly because of the different SSR search programs used and variations in the software parameter settings.…”
Section: Discussionmentioning
confidence: 95%
“…Because there are many GA and GT repeat motifs in wheat, eight wheat varieties have been scanned with designed primers using these motifs (Koike et al, 2006). GA was also shown to be the most abundant motif in grasses (Temnykh et al, 2001;Kantety et al, 2002;Nicot et al, 2004;Parida et al, 2006). It was revealed that the GA repeat motif has the highest polymorphism rate (approx.…”
Section: Discussionmentioning
confidence: 99%